Who owns you? : science, innovation, and the gene patent wars - Koepsell, David R. (David Richard) (Chichester, West Sussex, UK ; Malden, MA : John Wiley & Sons Ltd, 2015)
The 2nd Edition of Who Owns You, David Koepsell's widely acclaimed exploration of the philosophical and legal problems of patenting human genes, is updated to reflect the most recent changes to the cultural and legal climate relating to the practice of gene patenting. Lays bare the theoretical assumptions that underpin the injustice of patents on unmodified genes Makes a unique argument for a commons-by-necessity, explaining how parts of the universe are simply not susceptible to monopoly claims Represents the only work that attempts to first define the nature of the genetic objects involved.
Individual and collective rights in genomic data : preliminary issues -- Ethics and ontology : a brief discourse on method -- The science : genes -- DNA, species, individuals, and persons -- Legal dimensions in gene ownership -- BRCA 1 and 2 : the myriad case and beyond -- Are genes intellectual property? -- DNA and the commons -- Pragmatic considerations of gene ownership -- Nature, genes and the scientific commons : a social ontology of invention -- So, who owns you? : some conclusions about genes -- Property, and personhood.
Previous edition has subtitle: the corporate gold-rush to patent your genes.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Genes -- Patents; Human genetics -- Law and legislation; Intellectual property -- Moral and ethical aspects; Personality (Law); Biotechnology -- Patents; Genetics; Patent laws and legislation; LAW -- Administrative Law & Regulatory Practice; Genetics, Medical -- legislation & jurisprudence; Patents as Topic -- legislation & jurisprudence; Ownership -- ethics; Electronic books